Effects of AC Dielectric Barrier Discharge plasma actuator location on flow separation and airfoil performance - Bouremel, Y.; Li, J. M.; Zhao, Z.; Debiasi, Marco (Elsevier, 2014)
The goal of this work is to characterize the effect of Dielectric Barrier Discharge (DBD) plasma actuator on the lift and drag coefficients generated by the flow around a NACA 4415 airfoil model using force-balance and Particle Image Velocimetry (PIV) measurements. DBD actuators are mounted at the leading edge, at 30% and 60% of the chord length. The effect of actuation on the airfoil lift and drag at these different locations are studied. It is found that for increasing angles of attack, the actuators need to be located closer to the leading edge and in front of the separation area to produce the best lift or drag coefficient improvements. If located within the flow separation zone, their effects on the airfoil lift and drag coefficients are limited.
Keywords: Dielectric Barrier Discharge plasma; Particle image velocimetry; Vorticity; Lift coefficient; Drag coefficient; Separation point